Accuracy of a portable (ptz digital) camera system designed for aquatic three-dimensional analysis - Machtsiras, G.; Sander, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Three-dimensional (3D) motion analysis of aquatic activities such as swimming requires high accuracy throughout large volumes particularly when above and below water data are merged for full body analysis. The purpose of this study was to assess the accuracy of a recently developed portable camera system designed for 3D kinematic data collection of aquatic activities including swimming.